Physical health conditions and occupational risks among piano students and teachers in Chengdu, China: prevalence, awareness, and prevention strategies - Qing Yang; Chieko Mibu (Critical Public Health)
Playing-related musculoskeletal disorders (PRMDs) are a significant health concern for musicians, yet awareness and prevention strategies remain limited in many regions. In China, the physical health conditions of piano students and teachers have not been systematically examined, despite increasing demands on performance and practice. This study is grounded in interdisciplinary theoretical frameworks that combine music performance science and musicians’ well-being. A total of 205 piano students (170) and teachers (35) in Chengdu participated in an anonymous online questionnaire. Statistical methods, including frequency analysis and stepwise regression, were used to identify predictors of pain during piano playing. Results revealed that 100% of participants experienced discomfort, with the neck (30.7%), right forearm (37.6%), and right shoulder (32.7%) identified as common pain sites. The study found insufficient awareness of occupational diseases, with 34.2% of participants unfamiliar with typical conditions. Regression analysis identified four significant predictors of pain – right elbow (outer side) (p < 0.05), right wrist (thumb side) (p < 0.01), lower back (p < 0.05), and right forearm (p < 0.05) – accounting for 34.6% of the variance in pain levels. The findings demonstrate a critical need to raise awareness of occupational health risks, improve posture and biomechanics, and integrate somatic practices to help reduce injuries and enhance long-term healthy performance in China’s music education. These results also suggest the importance of future interdisciplinary research combining music, health, and technology to promote well-being among musicians.